2016
DOI: 10.1021/acs.nanolett.6b00902
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Clonal Analysis of Glioma-Stem-Cell Motility and Therapy Resistance

Abstract: Enhanced glioma-stem-cell (GSC) motility and therapy resistance are considered to play key roles in tumor cell dissemination and recurrence. As such, a better understanding of the mechanisms by which these cells disseminate and withstand therapy could lead to more efficacious treatments. Here, we introduce a novel micro-/nanotechnology-enabled chip platform for performing live-cell interrogation of patient-derived GSCs with single-clone resolution. On-chip analysis revealed marked intertumoral differences (>10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 40 publications
1
61
0
Order By: Relevance
“…Increasing evidence has indicated that acquired resistance to chemotherapy and radiation leads to the rapid recurrence and poor prognosis of glioma in patients . According to our results, MAP3K1 was the gene that was most correlated with TRIB2.…”
Section: Discussionsupporting
confidence: 56%
“…Increasing evidence has indicated that acquired resistance to chemotherapy and radiation leads to the rapid recurrence and poor prognosis of glioma in patients . According to our results, MAP3K1 was the gene that was most correlated with TRIB2.…”
Section: Discussionsupporting
confidence: 56%
“…These cells were plated on microtextured polydimethylsiloxane (PDMS) surfaces ( Fig. 1B), which were fabricated via replica molding from photolithographically fabricated silicon masters, and were designed as an array of parallel ridges and grooves with dimensions that have been previously tested in cancer cell dissemination studies (~2 µm × 2 µm with 2 µm spacing) [10][11][12][13] . MDSC motility was monitored at the single-clone level in real time via time-lapse microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…While targeting the dissemination-based mechanisms by which MDSCs infiltrate the tumor niche could be a viable alternative strategy against MDSC-driven immunosuppression at the tumor site, our understanding of such mechanisms for MDSCs is limited compared to what we know about the dissemination modalities of cancerous tumor cells. Structurally guided migration has been known to play a key role in the escape of cancerous cells from the primary tumor, as well as in dissemination and metastasis [10][11][12][13][14][15] . Nevertheless, to the best of our knowledge, no study has probed MDSC motility under structurally guided dissemination conditions.…”
mentioning
confidence: 99%
“…The intrinsic heterogeneity existed in almost any given cell population is a well-known confounding factor with important biological meanings. To properly address this variable and take the cellular heterogeneity into account in research, many platforms that allow biological samples to be analyzed at the single-cell level have been developed and have increasingly significant roles in the studies of genomics, transcriptomics, epigenomics, and proteomics relevant to different fields [57][58][59]. The heterogeneity of cells in a pathological lesion (e.g., a tumor) is likely to determine the therapeutic outcome and long-term prognosis in patients.…”
Section: Wearable Electroporation For Single-cell Transfectionmentioning
confidence: 99%